Tendon Stem/Progenitor Cell Subpopulations and Their Implications in Tendon Biology - Huang, Zizhan; Yin, Zi; Xu, Jialu; Fei, Yang; Heng, Boon Chin; Jiang, Xuesheng; Chen, Weishan; Shen, Weiliang (Frontiers in Cell and Developmental Biology, 2021)
Tendon harbors a cell population that possesses stem cell characteristics such as clonogenicity, multipotency and self-renewal capacity, commonly referred to as tendon stem/progenitor cells (TSPCs). Various techniques have been employed to study how TSPCs are implicated in tendon development, homeostasis and healing. Recent advances in single-cell analysis have enabled much progress in identifying and characterizing distinct subpopulations of TSPCs, which provides a more comprehensive view of TSPCs function in tendon biology. Understanding the mechanisms of physiological and pathological processes regulated by TSPCs, especially a particular subpopulation, would greatly benefit treatment of diseased tendons. Here, we summarize the current scientific literature on the various subpopulations of TSPCs, and discuss how TSPCs can contribute to tissue homeostasis and pathogenesis, as well as examine the key modulatory signaling pathways that determine stem/progenitor cell state. A better understanding of the roles that TSPCs play in tendon biology may facilitate the development of novel treatment strategies for tendon diseases.